Integration of Sundanese, Javanese, and Bantenese in Learning Yellow Books at Islamic Boarding Schools - Uyu Mu'awanah; Mahfud Mahfud; M. Syahbudin (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study examines the role and impact of Javanese and Sundanese languages in teaching the Yellow Book at Islamic boarding schools (pesantren) in Banten, with a focus on sociological, anthropological, and gender dimensions. The use of regional languages facilitates understanding among students and the surrounding community, as these languages are often their mother tongue and provide a more accessible medium for religious education. A qualitative descriptive case study approach was employed, integrating sociological and anthropological frameworks with a gender perspective. Data were collected through interviews, observations, and documentation, focusing on the linguistic practices in pesantren and their pedagogical implications. The findings reveal that pesantren in Banten leverage Javanese and Sundanese languages to teach the Yellow Book, ensuring effective knowledge transfer. These regional languages serve as a bridge between the kyai (teachers) and students, fostering comprehension and engagement. The learning methods, including sorogan and bandongan/wetonan, are integral to the sustainability of traditional pesantren and rely heavily on the effective use of regional languages for successful communication. The use of Javanese and Sundanese not only preserves local linguistic heritage but also enriches the pedagogical process in pesantren. The kyai’s deep understanding of classical texts, combined with their ability to communicate effectively in regional languages, enhances students’ learning experiences and strengthens cultural continuity. This study provides insights into the linguistic and pedagogical strategies employed in pesantren, highlighting the importance of regional languages in sustaining traditional Islamic education and fostering cultural identity in Banten.